The Contribution of the School Environment to the Overall Food Environment Experienced by Children. (17th May 2019) - Frisvold, David; Price, Joseph
Abstract : Despite the important role of schools in the food environment faced by children, most research examining access to healthy food has focused on the retail sector. We create a database of school menus and the nutritional information about each item on the menu from nearly all school districts in the United States to examine the influence of the school‐based food environment on the nutritional choices of children. Using the National Household Food Acquisition and Purchase Survey (FoodAPS), we find that, holding constant the neighborhood retail food environment, exposure to healthier meals at school increases the healthfulness of foods acquired by children throughout the day.